High-Voltage LiNi0.5Mn1.5O4 Cathode Stability of Fluorinated Ether Based on Enhanced Separator Wettability. Issue 8 (1st January 2019) - Zheng, Hao; Zhou, Xin; Cheng, Sheng; Xia, Ru; Nie, Shuping; Liang, Xin; Sun, Yi; Xiang, Hongfa
Abstract : Influence of separator wettability toward nonaqueous electrolyte was investigated in lithium-ion batteries using high-voltage LiNi0.5 Mn1.5 O4 cathode. A fluorinated ether of 1, 1, 2, 2-tetrafluoroethyl 2, 2, 3, 3-tetrafluoropropyl ether (HFE) was introduced as a co-solvent into the control electrolyte and polyolefin separator wettability toward nonaqueous electrolyte was effectively enhanced. Even though conductivity of the electrolyte bulk decreased after HFE was introduced, ionic conductivity of the electrolyte-soaking separator increased due to the enhanced separator wettability. From cycling stability of the half cells using high-voltage LiNi0.5 Mn1.5 O4 cathode, all electrolytes containing 10%, 20% and 30% HFE have superiority to the control electrolyte, and the 20% HFE containing electrolyte is the optimal. Microscopical analysis revealed that oxidative decomposition of HFE-containing electrolyte on the LiNi0.5 Mn1.5 O4 cathode was suppressed effectively with the thinner cathode electrolyte interface than that in the control electrolyte. In Li4 Ti5 O12 |LiNi0.5 Mn1.5 O4 full cells, the 20% HFE containing electrolyte exhibited the enhanced cycling stability and rate capability compared to the control of 1 mol L −1 LiPF6 /propylene carbonate. This work here reveals the effect of fluorinated ether co-solvent on separator wettability and further the superior separator wettability is critical to the oxidation stability of the electrolyte in lithium-ion batteries using high-voltage cathode.